Selection of specific cell wall antigen for rapid detection of fish pathogenic Vibrio parahaemolyticus by enzyme immunoassay - Shyne Anand, P. S.; Sobhana, K. S.; George, K. C.; Paul Raj, R. (Indian Journal of Fisheries, 2016)
An enzyme linked immunosorbant assay (ELISA) was developed, using polyclonal antibodies against a specific cell surface protein of Vibrio parahaemolyticus, for rapid detection of the organism. Nine virulent strains and one type strain ofÂ V. parahaemolyticus, one strain each of Vibrio vulnificus and Vibrio alginolyticus were used for the study. Cell surface proteins were extracted from all the strains and were analysed by SDS PAGE. One distinct band with molecular weight of 34 kDa, abundant in all the V. parahaemolyticus strains and lacks in other Vibrio species, was selected as cell wall antigen for immunisation. Polyclonal antibodies were raised against the selected 34 kDa protein of V. parahaemolyticus after preparative electrophoresis. An indirect plate ELISA was developed using this antiserum for detection of crude cell surface protein as well as whole cells of V. parahaemolyticus. All the 9 virulent strains and one type strain of V. parahaemolyticus tested, produced positive results, using the ELISA technique. To assess the specificity of the polyclonal serum, cross reaction studies with other Vibrio species such as V. vulnificus and V. alginolyticus were conducted by indirect plate ELISA. The results have clearly shown that antibodies directed against 34 kDa cell surface protein can be used for specific detection of fish pathogenic V. parahaemolyticus.